Registreringsrapport indre Finnmark 2011 - Skandfer, Marianne; Hood, Bryan (Septentrio Reports, 2018)
Archaeological survey report. Related publication: Skandfer, M., Blankholm, H. P. and Hood, B. (eds) (in press) Archaeological Perspectives on Hunter-Gatherer Landscapes and Resource Management in Interior North Norway. Equinox Publishing, Sheffield.